Lahar facies of the Latest Paleozoic Arbasay Formation: Geomorphological characters and paleoenvironment reconstruction of Northern Tian Shan, NW China. (1st December 2015) - Liu, Dongdong; Cheng, Feng; Guo, Zhaojie; Jolivet, Marc; Song, Yan
Highlights: A case study of volcanology that constrain the tectonic evolution in North Tian Shan. Discovery of syn-sedimentary normal faults in Late Paleozoic Arbasay Formation. The lithology characters of the lahars suggest of an alluvial fan context. They were deposited in small, normal faults bounded depocenters. Abstract: Texturally well-preserved lahars are exposed in the Latest Paleozoic Arbasay Formation, Northern Tian Shan. The lahars consist primarily of two lithofacies: massive, poorly lithified diamictites and stratified, moderately lithified gravelly sandstones. The diamictites can be generally divided into two subfacies, i.e., the matrix-supported and the clast-supported diamictites. Most diamictites are structureless and nongraded, however some crudely stratified beds with a certain grading have also been found. They are thick in beds and contain large clasts up to 3 m in dimension. The gravelly sandstones display much finer particle size and have wedge or lenticular geometries. Large clasts are absent within them and the sorting characters are much better than the diamictites. Despite the different size grading, the matrix and the clasts of the two lithofacies appear to be homogeneous. The matrix is generally sandy mudstone. The clasts comprise rhyolites, dacites, andesites, andesitic basalts and basalts, same to the co-existing volcanic rocks, suggesting they originate from the cognate volcanics. The disorganized diamictites are supposed to deposit from a turbulent flood or pyroclastic surge. The gravelly sandstone lithofacies are interpreted as sand-rich flood flows or hyperconcentrated flood flows during the waning stage of a mass-flow event. The overall characteristics of the deposits suggest a mass-flow dominated alluvial fan environment. They are rapidly accumulated within small, normal faults bounded depocenters. The characteristics of the Arbasay Formation lahars, together with the geochemistry characters of the co-existing volcanic rocks, clearly prove that they were deposited in a post-collisional extensional regime. LA-ICP-MS zircon dating of the intercalated fallout tuff sample provided an age of 314.4 ± 3.4 Ma (MSWD = 1.6), suggesting they were deposited at Late Carboniferous. Therefore, the North Tian Shan Ocean must have closed before 314 Ma, and the initial basin type in Northern Tian Shan should be extensional faulted basins rather foreland basins.